Equity research - corsair gaming Inc: main trends and analysis - Pato, Francisco Maria Casella Vaz (2022)
This equity research report aims at Corsair Gaming Inc. This report analyses the company and its strategy, while discussing its fit within the Gaming Components and Systems, and Gamer and Creator Peripherals industries, taking into consideration the valuation objective. A series of important trends are afterwards examined, as well as a peer financial analysis. Both chapters treat important determinants for the future of the company and most of its conclusions are used as drivers in the valuation.